Observer Design For Underwater Glider - Oo, Fhong Hao (2014)
Underwater gliders have numerous advantages over the conventional underwater vehicles in oceanographic applications. Gliders offered long duration and long range missions with low energy consumption. Internal actuation design protected actuators from ocean environment and have higher durability. Autonomous control strategies and path planning have been proposed by researchers. Controller for glider system required information from the system sensed outputs to perform closed-loop system. However some of the system states are difficult and unable to be measured during underwater and they are needed to be estimated. Presently the glider states estimation are based on assumption of constant angle of attack, pitch angle and so on. But this states estimation technique is lack of accuracy. To overcome this, linear observer has been proposed to estimate the unmeasured states and improved the estimation accuracy. However the states estimation by linear observer is only accurate for observation on linear model with motion close to equilibrium glide. For states estimation on nonlinear dynamic and all glide path aspect, nonlinear glider model based observer design is desired.